“My childhood affected my ability to be resilient in both good and bad ways”: A mixed methods examination on the links between adverse childhood experiences, resilience, and transactional sex among young South African women - Deborah Baron; Nisha Gottfredson O’Shea; Alexandra Lightfoot; Caroline Kuo; Sheri Lippman; F. Xavier Gómez-Olivé; Kathleen Kahn; Audrey Pettifor; Suzanne Maman (PLoS ONE, 2026)
Background South African women are disproportionately impacted by HIV. Among these women, adverse childhood experiences (ACEs) are common and have been linked to HIV risk behaviors, including transactional sex (TS). Resilience—or multi-level processes related to overcoming adversity—provides a strengths-based lens that may buffer effects between ACEs and TS. Methods We conducted a convergent mixed methods study among women aged 18–25 years in Mpumalanga, South Africa. We used logistic regression to assess the association between ACEs and TS; and tested moderation effects of five resilience scales across social-ecological levels hypothesized to dampen the effect of ACEs on TS. In parallel, we conducted a photovoice study that utilized participant-generated images and narratives, and thematic and sequence analysis to explore how women exposed to ACEs perceive and use resilience to navigate TS relationships. Results Our analysis included 1,222 women aged 18–25 years, of whom 714 (58.43%) reported ACE exposure, with 519 (42.47%) reporting 1–2 ACEs and 195 (15.96%) reporting ≥3 ACEs; 340 (27.82%) reported TS. Women reporting ACE exposure had increased odds of TS compared to those without ACE exposure, controlling for confounders (AOR = 1.52, 95% CI: 1.17–1.99, P = 0.002). Among women with histories of ACEs, women with ≥3 ACES had 2.55 times the odds of TS than those reporting 1–2 ACEs (95% CI: 1.79–3.63, P=<0.001). None of the resilience measures moderated effects between ACEs and TS. Through the photovoice study (n = 10), women described how ACEs necessitated resilience early in life; some applying it to avoid and others to sustain TS relationships. Conclusion We examined the interplay between resilience, ACEs, and TS. Although quantitative results showed resilience did not buffer negative effects of ACEs on TS, the photovoice findings suggest resilience was salient and influential in women’s lives. Future research should explore resilience measures and interventions that address the complex gender and power dynamics that exacerbate women’s exposure to TS and HIV.